Is Portugal an accessible tourist destination? Factors that influence the perception of disabled people regarding Portugal as an accessible tourist destination - Gomes, Andreia Filipa Castrelas (2022)
Tourism is a fast-growing sector that has become, in recent years, one of the most important sectors in the world economy. Given its relevance, there is a need to make tourism more accessible, less unequal and able to be experienced by all individuals. It is estimated that about two billion people are affected, directly or indirectly, by some kind of disability. Thus, Accessible Tourism emerges not only as something essential to achieve equality, but also as an excellent opportunity for economic development. However, there is a lack of interest on the part of companies and governments in finding solutions to mitigate the multiple barriers that disabled people continue to encounter in their participation in tourism. This dissertation aims to understand (i) the perception of people with disabilities regarding accessibility in tourism in Portugal (ii) how some factors impact this evaluation. For this purpose, a questionnaire based on Conceptual Work derived from the literature was developed and, subsequently, a quantitative methodology was used to analyze the results. A total of 136 valid answers were obtained, which allowed for the descriptive analysis of the results, as well as to test the hypotheses presented through a linear regression. Based on the developed analysis, it was possible to verify that the perception of people with disabilities and their caregivers about Portugal as an accessible tourist destination is not quite positive and it was possible to prove that the characteristics of the destination - Physical, Information Safety and Hospitality - have a positive impact on that perception.